HUBUNGAN MINAT BELAJAR DAN KEBIASAAN BELAJAR SISWA DENGAN HASIL BELAJAR GEOGRAFI SISWA KELAS XI IPS SMA NEGERI 1 V KOTO KAMPuNG DALAM - Wia Amelia; Rahmanelli Rahmanelli (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to obtain data and information about the relationship between learning interest and learning outcomes, the relationship between learning habits and learning outcomes, the relationship between learning interest and learning habits with the Geography learning outcomes of class XI students of SMAN 1 V Koto Kampung Dalam. This research uses descriptive correlation method. The study population was all students of class XI SMAN 1 V Koto Kampung Dalam, totaling 120 students. The sample determined by the Proportional Random Sampling technique represents 40% of the 120 population, so the sample is 48 students. The data were analyzed using three steps, namely: (1) Descriptive analysis which aims to see the average (mean), standard deviation and percentage, and (2) Test requirements analysis in the form of normality, homogeneity and multicollinearity tests (3) inferential analysis for hypothesis testing. The results showed that: (1) There is a significant and positive relationship between student interest in learning and learning outcomes of Geography class XI students of SMAN 1 V Koto Kampung Dalam, categorized as strong with a contribution of 57.2%. (2) There is a significant and positive relationship between the students' study habits and the Geography learning outcomes of class XI students of SMAN 1 V Koto Kampung Dalam, categorized as strong with a contribution of 47.0%. (4) There is a significant and positive relationship between students' interest and study habits with the Geography learning outcomes of class XI students of SMAN 1 V Koto Kampung Dalam, categorized as very strong with a contribution of 64.7%. Keywords : interest in learning, study habits, learning outcomes